8 - Book Reviews: Archie Mafeje, The Theory and Ethnography of African Social Formations: The Case of Interlacustrine Kingdoms , Dakar, CODESRIA, 1991, 170pp. - Amin, Samir (Africa Development, 1994)
Abstract